The social dimension of language. A review of the literature - Michał Bergier; Izabela Karpiszuk (Rozprawy Społeczne)
Introduction Language is a rapidly developing, dynamic and living phenomenon. It is one of the most important elements of culture, directly related to the traditions of individual societies, as well as to everyday life and social relations. Language can both integrate and divide a society. Sociolect, jargon, or slang can be what distinguishes individual social groups, binds the people belonging to them together, and sets values that sometimes oppose the commonly held ones. Language can also be an important component in the formation of niche groups, and people belonging to them can find a safe space, support and a way to express their emotions or needs with the help of language. The paper undertakes an analysis of the literature, on the basis of which language is shown to be an important social element. Recent, as well as classic approaches to such issues as sociolinguistics, sociolekt, jargon and slang, and their impact on societies are presented.